THE PRACTICE OF JUAL SEADANYA IN THE BANJAR COMMUNITY: Between Islamic Legal Culture and Consumer Protection in Modern Transactions - Rahmaniah, Amelia (Fakultas Syariah, 2025)
Modern buying and selling transactions demand extreme caution from both sellers and buyers, as many problems stem from a lack of caution. This caution has long been practiced by the Banjar community in the form of the expression